Correlation of Numerical and Experimental Analysis for Dynamic Behaviour of a body-in-white (BIW) Structure - N. A. Z., Abdullah; M. S. M., Sani; M. M., Rahman; Izzuddin, Zaman (EDP Sciences, 2017)
In order to determine the reliability of data gathered using computational version of finite element analysis, data obtained through experimental work are always utilized. In field of dynamic analysis, experimental data is often viewed for having better accuracy giving the availability of reliable data acquisition and measuring equipment. On the other hand, in case of finite element deviation, it can sometimes be considered as inaccurate especially subject to complex structure such as body-in-white. This is due to difficulties that might occur in modelling of joints, boundary conditions and damping of the structure. In this study, a process of comparison and validation of model based test design with modal testing results was conducted. Modal properties (natural frequencies, mode shapes, and damping ratio) of a body-in-white structure were determined using both experimental modal analysis (EMA) and finite element analysis (FEA). Correlation of both sets of data was performed for validation. The discrepancies that appear after correlation was then reduced by performing model updating procedure. The results presented here may demonstrate the effectiveness of model updating technique on improving the complex structure such as body-in-white structure.